Armenian arj ‘bear’ - Werner Winter (Sound Law and Analogy, 1997)
Purpose To describe the arthroscopic "mooring" technique for the treatment of large anterior glenoid rim fractures and report the clinical and radiological outcomes of a consecutive case series treated with this technique. Methods This retrospective study was conducted between January 2016 and August 2023. Eligible patients were those with acute anterior glenoid rim fracture (≥20% glenoid width involvement, displacement >5 mm) who underwent the "mooring" technique. All completed preoperative, 1-day postoperative, and 6-month postoperative computed tomography scans, as well as radiographs and clinical follow-up for a minimum of 2 years. Clinical outcomes were assessed using the American Shoulder and Elbow Surgeons score, Constant-Murley score, Rowe score, the Single Assessment Numeric Evaluation, and visual analog scale for pain. Radiographic parameters included reduction quality, bone union, and glenohumeral osteoarthritis progression. Results A total of 56 patients was included in the final analysis (40 men, 16 women; mean age, 46.8 ± 16.2 years). The mean follow-up period was 27.2 ± 2.9 months. At the final follow-up, the mean American Shoulder and Elbow Surgeons, Constant-Murley, Rowe scores, Single Assessment Numeric Evaluation, and visual analog scale for pain were 89.5 ± 6.4, 90.3 ± 6.0, 89.6 ± 4.5, 83.2 ± 8.5, and 1.1 ± 1.0 points, respectively. Range of motion of the affected shoulder differed from the contralateral side: anterior flexion deficit -8° (P < .001), external rotation deficit -6° (P < .001), and internal rotation (P < .001). Bone union rate was 100% at 6 months postoperatively (66.1% complete, 33.9% partial). Satisfactory reduction quality (grade I/II) was achieved in 52 (92.9%) cases. Four patients (7.1%) showed glenohumeral osteoarthritis progression at the final follow-up. Conclusions The arthroscopic "mooring" technique for large anterior glenoid rim fractures yields satisfactory 2-year short-term outcomes, featuring favorable reduction quality, a high bone union rate, and good clinical functional recovery. Level of evidence Level IV, retrospective case series.